2017
DOI: 10.1177/0969733017739783
|View full text |Cite
|
Sign up to set email alerts
|

Truth-telling, decision-making, and ethics among cancer patients in nursing practice in China

Abstract: Treating each family individually to explore the family's beliefs and values on this issue is essential in healthcare practice and nurses should tailor their own approach to individual needs regarding truth-telling in different situations. Moreover, the Chinese Code of Ethics should be modified to be more specific and applicable. Finally, a narrative ethics approach should be applied and teamwork between nurses, physicians and families should be established to support cancer patients and to ensure their autono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…According to the International Committee of Nurses (ICN) Code of Ethics, in order to avoid mistakes in nursing interventions, nurses are expected to provide sufficient information about nursing interventions to patients and to act in accuracy and fairness to protect the rights of patients under any conditions. 23 Code of Ethics specified by ICN is accepted without any change in Turkey. In Turkey, nurses are also supposed to perform the tasks given by doctors.…”
Section: Discussionmentioning
confidence: 99%
“…According to the International Committee of Nurses (ICN) Code of Ethics, in order to avoid mistakes in nursing interventions, nurses are expected to provide sufficient information about nursing interventions to patients and to act in accuracy and fairness to protect the rights of patients under any conditions. 23 Code of Ethics specified by ICN is accepted without any change in Turkey. In Turkey, nurses are also supposed to perform the tasks given by doctors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that patients or family members might think that physicians are too busy and prefer to ask nurses about the truth about their illnesses, which creates an ethical dilemma for nurses regarding whether and how to reveal the truth . Ten years ago, Li's study found that 55.8% of Chinese nurses thought that a terminal diagnosis should not be disclosed, but Ling's study concluded that to ensure that nurses practice ethically, a narrative ethics approach should be applied and teamwork between nurses, physicians, and families should be established to support cancer patients and ensure their autonomy . Nurses play a vital role in CDD.…”
Section: Introductionmentioning
confidence: 99%
“…21-23 Ten years ago, Li's study found that 55.8% of Chinese nurses thought that a terminal diagnosis should not be disclosed, but Ling's study concluded that to ensure that nurses practice ethically, a narrative ethics approach should be applied and teamwork between nurses, physicians, and families should be established to support cancer patients and ensure their autonomy. 24,25 Nurses play a vital role in CDD. However, little evidence is available describing the oncology nurses' experiences with CDD.…”
mentioning
confidence: 99%
“…Communication with patients and relatives can be complex, being one of the largest challenges palliative care professionals, especially nurses, face across cultures. 106,107 To accomplish palliative care’s mission to assist and guide patients throughout all phases of treatment and care, maintaining his or her integrity and dignity, patients need indeed to understand their condition and be guided to take an active role in their care plan, considering his or her values, goals, preferences, and wishes. 107 110…”
Section: Discussionmentioning
confidence: 99%